2002
DOI: 10.4049/jimmunol.169.6.3293
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Type 1 Immunity After Secondary Viral Challenge in Mice Primed as Neonates

Abstract: The goal of infant immunization against viral infection is to develop protective long term memory responses. Priming neonatal mice with a low dose of Cas-Br-E murine leukemia virus (Cas) results in adult-like, type 1 protective responses. However, other studies suggest that Ag priming of neonates leads to an increase in type 2 secondary responses even when primary responses were type 1. We assessed whether type 1 CD8+ T cell-mediated responses developed in murine neonates are maintained after secondary challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
(76 reference statements)
1
19
1
Order By: Relevance
“…We interpret these findings as induction of RSV‐specific Th2 memory responses after neonatal RSV infection. Other investigators have shown, in a model of neonatal priming with murine leukaemia virus, a transient production of IL‐4 after secondary viral challenge [28]. However, this IL‐4 production was not virus‐specific and subsided 3 weeks after challenge.…”
Section: Discussionmentioning
confidence: 96%
“…We interpret these findings as induction of RSV‐specific Th2 memory responses after neonatal RSV infection. Other investigators have shown, in a model of neonatal priming with murine leukaemia virus, a transient production of IL‐4 after secondary viral challenge [28]. However, this IL‐4 production was not virus‐specific and subsided 3 weeks after challenge.…”
Section: Discussionmentioning
confidence: 96%
“…CD8 + cell function in neonates has been mostly studied in response to infection with viruses, including influenza virus (25, 26), herpes simplex virus (2729), respiratory syncytial virus (30), cytomegalovirus (31, 32), lymphocytic choriomeningitis virus (33), adenovirus (34), and Cas-Br-E murine leukemia virus (3537). Most often, these viruses have been introduced either systemically or through a pulmonary route.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous investigations into the neonatal memory response were performed using models of chronic infection. These studies found that neonate-primed CD8 + T cells develop into cells that rival adult-primed cells in proliferation and effector function in a murine leukemia virus model of chronic viral infection (47, 48). However, such chronic infections due to the sustained presence of high antigen loads do not reflect true memory, and may not be informative on memory generation after an acute infection that is followed by antigen clearance.…”
Section: Discussionmentioning
confidence: 99%